Rancang Bangun Sistem Peringatan Dini Untuk Pencegahan Virus Covid 19 Melalui Deteksi Suhu Tubuh Secara Real Time Berbasis Informasi Suara - Wafi Arifin; Sugeng Murdowo; Fata Nidaul Khasanah (Jurnal Kajian Ilmiah, 2025)
The Covid 19 disease outbreak has recently increased its spread in Indonesia in particular. This makes Indonesia tighten its health protocols, especially body temperature because the Covid 19 virus is the most visible symptom, namely temperatures above 37.5 Celsius, and it is prohibited to be close to between individuals. So far, the thermometer sold in the market is a thermometer that still uses human assistance. To help and solve this problem, a non-contac temperature thermometer tool was made by applying the Gy-906 sensor to find out what a person's temperature is and an ultrasonic sensor to replace the button on a conventional thermometer. This tool is designed using an Arduino UNO Atmega 328 microcontroller. The Gy-906 sensor will read body temperature by bringing the forehead or palm closer and Ultrasonic to help the Gy-906 sensor detect body temperature in front of the sensor. Then the Arduino UNO will process the data and will display on the 16x2 LCD and the speaker output of the temperature detection results will be followed by a temperature statement on the LCD and a temperature statement via the speaker.